Max Steiner : composing, Casablanca, and the golden age of film music - Wegele, Peter (Rowman and Littlefield, 2014)
This biography of Steiner provides insight into how the film music industry worked and functioned during the Golden era of film scores. The central part of this work is an analysis of Steiner's score to Casablanca from a musician's point of view. The author also compares Steiner's work with several of his contemporaries, including Hugo Friedhofer, Erich Wolfgang Korngold, Alfred Newman, and Franz Waxman.